2014
DOI: 10.1002/ca.22410
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical observations of the human acromioclavicular joint

Abstract: The condition of the acromioclavicular joint (ACJ) is considered to be one factor in the etiology of shoulder impingement syndrome, but there are few supporting morphological data. Fifty-two sides of 35 cadavers were investigated macroscopically and histologically using Safranin O, Fast green, and Weigert's iron hematoxylin staining. The ACJs were classified into three major types depending on the presence or absence of the articular disk. In type 1, the articular disk divided the articular cavity completely (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
7
0
2
Order By: Relevance
“…A proportion of 37 % showed no articular disc or only remnants of an articular disc. Histological studies have confirmed that the articular disc is confluent with the superior capsular-ligamentous structures forming an anatomical-biomechanical unit [6, 27]. Hereby, the articular disc seems to function as a biomechanical reinforcement of the superior ACLC.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A proportion of 37 % showed no articular disc or only remnants of an articular disc. Histological studies have confirmed that the articular disc is confluent with the superior capsular-ligamentous structures forming an anatomical-biomechanical unit [6, 27]. Hereby, the articular disc seems to function as a biomechanical reinforcement of the superior ACLC.…”
Section: Discussionmentioning
confidence: 98%
“…If present, the articular disc may vary in size and appearance [6, 27]. The deltoid-trapezoidal (DT) fascia inserts on the superior lateral clavicle and superior ACLC providing additional biomechanical reinforcement [31].…”
Section: Introductionmentioning
confidence: 99%
“…In a cadaveric study, Emura et al (2014) classified the acromioclavicular joint into three major types according to the presence or absence of the articular disc.…”
Section: Acromioclavicularmentioning
confidence: 99%
“…Vermeintlich nicht ausreichende Repositionen können bei Vergleich mit der (unverletzten) Gegenseite in einigen Fällen als Normalbefund eingestuft werden. Die Reposition selbst kann aber auch durch die Konfiguration des ACG selbst erschwert sein, da es verschiedene Varianten des Diskus und der Formschlüssigkeit der lateralen Klavikula zur Gelenkfläche am Akromion gibt [12].…”
Section: » Die Klassifikation Nachunclassified
“…Die knöchernen Gelenkpartner sind mit hyalinem Knorpel über-zogen. Im Gelenkspalt befindet sich ein fibrokartilaginärer Diskus unterschiedlicher Größe und Form [7,12]. Die Stabilität des Gelenks wird durch die ACGKapsel und durch die korakoklavikulä-ren(CC)-Bänder gewährleistet.…”
Section: Anatomie Und Biomechanikunclassified